Posterior reversible encephalopathy syndrome: An uncommon sequelae of Eclampsia - Biswas, Jhuma; Banerjee, Prosenjit; Datta, Mallika; Bhattacharya, Namrata; Maitra, Arghya; Mitra, Divyangana; Ghosh, Utsa (Asian Journal of Medical Sciences, 2022)
Posterior reversible encephalopathy syndrome (PRES) refers to a clinical neuro-radiologic entity with characteristic features on neuro-imaging depicting posterior cerebral white matter edema. Clinical symptoms include headache, visual disturbances, confusion, and seizures. We report six cases of acute PRES who had eclampsia and presented with recurrent episodes of convulsions and hypertension. Magnetic resonance imaging scan showed diffuse abnormal signal intensities involving deep white matter of occipital region. Follow-up examination after 2 weeks of conservative management, showed marked improvement clinically and on neuro-imaging following which patients were discharged in stable condition.